Public Debts of Europe (Quarterly Journal of Economics, 1887)
Journal Article Public Debts of Europe Get access The Quarterly Journal of Economics, Volume 1, Issue 3, April 1887, Pages 358–359, https://doi.org/10.1093/qje/1.3.358 Published: 01 April 1887